Researching conflict in Africa : insights and experiences - Porter, Elisabeth J. (United Nations University Press, 2005)
"Parts of Africa experience persistent violence and seemingly intractable conflicts. These generally have deep historical roots dating to colonial periods and before, and many of them have become more destructive in the post-Cold war period. These violent conflicts have drawn researchers seeking to determine and explain why conflicts are prevalent, what makes them intensify, and how conflicts can be resolved. However much of the literature on research methodology does not address the complexities of conducting research in the midst of violent conflict and massive ethno-political disputes. This book directly addresses these issues. It examines the ethical and practical issues of researching within violent and divided societies. It provides fascinating and factual case studies from Angola, the Democratic Republic of Congo, Ghana, Nigeria, Rwanda and South Africa. The authors provide insights about researching conflict in Africa that can only be gained through fieldwork experience. This book is of interest to all researchers interested in Africa and to those involved in research about, and within, societies experiencing conflict and violence."